Chinese immigrants in the US labor market: Effects of post-tiananmen immigration policy - Pia M. Orrenius; Madeline Zavodny; Emily Kerr (Institute for the Study of Labor (IZA), 2012)
The Tiananmen Square protests in 1989 and ensuing government crackdown affected Chinese nationals not only at home but around the world. The U.S. government responded to the events in China by enacting multiple measures to protect Chinese nationals present in the U.S. It first suspended all forced departures among Chinese nationals present in the country as of June 1989 and later gave them authorization to work legally. The Chinese Student Protection Act, passed in October 1992, made those Chinese nationals eligible for lawful permanent resident status. These actions applied to about 80,000 Chinese nationals residing in the U.S. on student or other temporary visas or illegally. Receiving permission to work legally and then a green card is likely to have affected recipients' labor market outcomes. This study uses 1990 and 2000 census data to examine employment and earnings among Chinese immigrants who were likely beneficiaries of the U.S. government's actions. Relative to immigrants from Hong Kong, Taiwan, and South Korea - countries not covered by the post-Tiananmen immigration policy measures - highly-educated immigrants from mainland China experienced significant employment and earnings gains during the 1990s. Chinese immigrants who arrived in the U.S in time to benefit from the measures also had higher relative earnings in 2000 than Chinese immigrants who arrived too late to benefit. The results suggest that getting legal work status and then a green card has a significant positive effect on skilled migrants' labor market outcomes.
urn:nbn:de:101:1-201203145375
Keywords: J15; 330; immigration; Chinese Student Protection Act; employment; earnings; Migranten; Chinesen; Migrationspolitik; Berufliche Integration; Einkommen; USA; Politische Unruhen; China